Answer:
x = -6
Explanation:
We recognize that 25 = 5^2 and also 125 = 5^3, thus we can write:
![25^(2x+3)=125^x\\(5^2)^(2x+3)=(5^3)^x](https://img.qammunity.org/2020/formulas/mathematics/high-school/7ujn8ed6nf2md63eibqkgse05ii9u0ca9n.png)
Now we can use the property of exponents [
] to simplify it:
![(5^2)^(2x+3)=(5^3)^x\\5^(2(2x+3))=5^(3x)\\5^(4x+6)=5^(3x)](https://img.qammunity.org/2020/formulas/mathematics/high-school/kv8bx7oj42tr6i97m4ll0zvmby3h3z0qtu.png)
We equate the exponents (since we have similar base) to find the value of x:
4x + 6 = 3x
4x - 3x = -6
x = -6